Essays on non-search unemployment and monetary policy - Vähämaa, Oskari (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku, Turku School of Economics|, 2018)
This doctoral dissertation explores the role that institutions and policies can have in shaping aggregate economic outcomes. The thesis is comprised of an introductory chapter and three independent essays. All essays set up a clear structure that specifies how economic agents react to a changing environment. That is, each essay builds on the general equilibrium modeling of Macroeconomics. The first essay examines the equilibrium effects of occupational human capital protection during mass layoffs in a setup where human capital can depreciate during unemployment spells and commitment problems prevent markets from allocating layoffs optimally. As the consequences of the policy are tightly related to occupational mobility, the paper focuses on modeling reallocation incentives of heterogeneous workers. In a calibrated model, a policy that concentrates involuntary unemployment incidences to inexperienced workers, decreases workers’ incentives to reallocate, compared to an equilibrium where everyone faces an identical unemployment risk, leading also to a decrease in aggregate unemployment. Moreover, this policy change increases the market output and on average does not harm the inexperienced workers. The second essay explores the effects of unionization in an island model of Lucas and Prescott (1974) with different union structures. When a model with competitive labor markets is set to match the empirical fact that a large number of unemployment spells ends with recalls, an introduction of a large labor union, that represents all workers and sets a common economy-wide minimum wage, increases unemployment substantially. Moreover, the whole increase is about non-search unemployment as search unemployment actually reduces marginally. If the same degree of unionization is generated by a continuum of small unions, the aggregate unemployment reaction is somewhat smaller. However, the increase in non-search unemployment is still considerable. The workings of a large union are also explored when the union is assumed to bargain over the minimum wage with an employers’ organization. This environment leads to a considerably lower increase in aggregate unemployment. Yet again, the search intensity of unemployed workers drops significantly. In the third essay we show that the cancellation of income and substitution effect implied by King-Plosser-Rebelo (1988) preferences breaks tight coeff- cient restriction between the slope of the Phillips curve and the elasticity of consumption with respect to real interest rate in a sticky price macro model. This facilitates the estimation of intertemporal elasticity of substitution using full information Bayesian Maximum Likelihood techniques within a structural model. The US data from the period 1984–2007 supports low intertemporal elasticity of substitution and strongly rejects a logarithmic and an additively separable utility specification commonly applied in the New Keynesian literature.

Tämä väitöskirja tarkastelee instituutioiden ja politiikkatoimenpiteiden vaikutuksia koko talouden tulemien kannalta, keskittyen erityisesti työmarkkinoihin. Työ koostuu johdannosta ja kolmesta itsenäisestä esseestä. Tarkastelu pohjautuu yleisen tasapainon malleihin. Ensimmäinen essee tutkii ammatillisen osaamisen suojelun vaikutuksia irtisanomistilanteissa, kun inhimillinen pääoma voi rapautua työttömyysjaksojen aikana ja epätäydellisistä sopimuksista johtuen markkinat eivät kohdista irtisanomisia tehokkaasti. Koska politiikkamuutoksen seuraukset ovat läheisesti sidoksissa ammatilliseen liikkuvuuteen, essee keskittyy heterogeenisten työntekijöiden uranvaihtojen mallintamiseen. Kalibroituun malliin pohjautuvat tulokset indikoivat, että irtisanomissääntö, joka kohdistaa työttömyysjaksot ensisijassa kokemattomiin työntekijöihin, laskee ammattien välistä liikkuvuutta verrattuna tilanteeseen, jossa kaikki työntekijät kohtaavat saman työttömyysriskin. Toisaalta talouden työttömyys on pienempää ja tuotanto suurempaa, kun irtisanomiset kohdistuvat kokemattomiin työntekijöihin. Väitöskirjan toinen luku tarkastelee erilaisten ammattiliittorakenteiden merkitystä Lucasin ja Prescottin (1974) mallin avulla. Kun kalibroinnissa huomioidaan, että suuri osa työttömyysjaksoista päättyy paluuseen samalle työnantajalle, suuren ja kaikkia työntekijöitä edustavan ammattiliiton vaikutus minipalkkaan ja työttömyyteen on merkittävä. Lisäksi koko työttömyyden lisäys on työnhaun poissulkevaa työttömyyttä. Jos vastaava järjestäytymisaste saavutetaan monien ammattiliittojen toimesta, työttömyyden ja minimipalkan reaktiot ovat pienempiä. Kuitenkin myös tässä tapauksessa työnhaun poissulkevan työttömyyden kasvu on huomattavaa. Tutkimuksessa tarkastellaan myös tilannetta, jossa suuri ammattiliitto neuvottelee minimipalkasta työnantajajärjestön kanssa. Tässä tapauksessa työttömyyden reaktiot ovat selvästi maltillisempia. Kolmannessa esseessä tarkastellaan uuskeynesiläistä mallia, jossa työn tarjonnan tulo- ja substituutiovaikutus kumoavat toisensa, kun taloudenpitäjien preferenssejä kuvataan tasaisen kasvun mukaisilla ns. King–Plosser–Rebelopreferensseillä (1988). Tällöin talouden inflaatiodynamiikkaa kuvaavan Phillips-käyrän kulmakertoimen – inflaation kustannusherkkyyden – ja kulutuksen korkojouston välinen tiivis yhteys rikkoontuu. Tämä ominaisuus helpottaa kulutuksen kasvuvauhdin korkoherkkyyttä mittaavan parametrin eli intertemporaalisen substituutiojouston estimointia rakenteellisissa malleissa, kun estimoinneissa käytetään täyden informaation bayesilaista suurimman uskottavuuden estimointimenetelmää. Yhdysvalloista kerätyssä, ajanjakson 1984–2007 kattavassa aineistossa intertemporaalisen substituutiojouston arvo estimoituu pieneksi.